RELASI PATRON-KLIEN DAN PRAKTIK OLIGARKI LOKAL DALAM SISTEM KEPEMIMPINAN MASYARAKAT DESA DI JAWA TENGAH - Fike Windi Nufria Wati; Kuncoro Bayu Prasetyo (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study examines the patron-client relationship between local business owners and village heads, which began during the village head election campaign and gave rise to local oligarchic practices within the local leadership system in rural Central Java, specifically in Gowak Village, Temanggung Regency. This research aims to identify the causal factors and forms of the patron-client relationship between business owners and village heads, as well as the emergence of local oligarchic practices as a consequence of this patron-client relationship within the village leadership system. The study employed a qualitative methodology using a case study in Gowak Village, Temanggung Regency. Data were collected through interviews and direct observation in the field. Data analysis was conducted using James Scott’s patron-client theory and Winters’oligarchy theory. The study reveals that the patron-client relationship formed between the landowner and the village head as the primary mechanism for securing votes during village head elections persists throughout the village head’s tenure. This patron-client relationship ultimately gives rise to local oligarchic practices within the village head’s leadership system, where the village head can be influenced by the landlord’s interests, both in terms of infrastructure development and localpolitical policies decided by the village head.